Power allocation in MIMO radars based on LPI optimisation and detection performance fulfilment - Ghoreishian, Mohammad Javad; Hosseini Andargoli, Seyed Mehdi; Parvari, Fatemeh (IET radar, sonar & navigation, 2020)
In this study, the issue of power allocation in the statistical multiple-input–multiple-output (MIMO) radars is investigated to reduce the probability of interception. In MIMO radars, orthogonal waveforms are commonly used, in which waveforms are orthogonal frequency-diversity or phase-coded (PC) waveforms. Therefore, the low probability of intercept (LPI) optimisation problem is considered for different orthogonal signals separately. In the FD case, the LPI optimisation problem based on analysing signal processing applied to the conventional interceptor is formulated as a min–max problem. In the PC case, the problem is formulated as a sum power minimisation problem with non-convex and non-linear detection performance constraint. Some relaxations and innovations are applied to simplify the problem and to convert it to a convex-linear problem. In addition, by analysing the form of the proposed solution, the proposed algorithm is extended based on adaptive thresholding to improve the LPI performance as much as possible. Here, the original problem is solved by a standard log-barrier algorithm as a benchmark to verify the optimality of the proposed algorithms. Simulation results show that, the proposed algorithms guarantee not only the detection performances, but also the LPI performance is considerably better in comparison with traditional power allocation algorithms.